Load Optimization of Heat Exchanger Cascades - Sipal, J. (Elektronika ir Elektrotechnika, 2011)
This paper explores the load variant efficiency of heat exchangers. An empirical model of efficiency as a function of heat exchanger load is presented. This model can be used to optimize the load distribution among heat exchangers in heat exchanger cascades. As a result, the efficiency of district heat exchanger stations can be significantly increased. The efficiency increase depends on the load but it can be approximately doubled for a significant interval of loads. Ill. 4, bibl. 5, tabl. 2 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.109.3.179